Interaction of public and private employment: evidence from a German government move - Faggio, Giulia; Schlüter, Teresa; vom Berge, Philipp (London, 2018)
"We use the German government move from Bonn to Berlin in 1999 to test competing views about the impact of public employment on private sector activity in a local labor market. A relocated public sector job might create new jobs in an area as it increases demand for locally-produced goods and services, or crowd out existing jobs due to upward pressure on housing rents. Using employment data from a panel of a 50% sample of establishments across 190 Berlin postcodes, we apply a treatment intensity approach which takes the possibility of spillovers into account. Results indicate that the arrival of 100 public sector jobs into an area generates 55 additional jobs in the private sector. There is evidence of spillovers: relocations up to a distance of 1km from a postcode boundary increases employment in the private sector by 36 jobs. These effects are coming through job gains in the service sector, while manufacturing employment is not influenced by the relocation. "